Stimulated chiral light-matter interactions in biological microlasers - Yuan, Zhiyi (2022)
Chiral light-matter interactions have emerged as a promising area in biophysics and quantum optics. Great progress in enhancing chiral light-matter interactions have been investigated through passive resonators or spontaneous emission. Nevertheless, the interaction between chiral biomolecules and stimulated emission remains unexplored. Here we introduce the concept of a biological chiral laser by amplifying chiral light-matter interactions in an active resonator through stimulated emission process. Green fluorescent proteins or chiral biomolecules encapsulated in Fabry-Perot microcavity served as the gain material while excited by either left-handed or right-handed circularly polarized pump laser. Owing to the nonlinear pump energy dependence of stimulated emission, significant enhancement of chiral light-matter interactions was demonstrated. Detailed experiments and theory revealed that a lasing dissymmetry factor is determined by molecular absorption dissymmetry factor at its excitation wavelength. Finally, chirality transfer was investigated under a stimulated emission process through resonance energy transfer. Our findings elucidate the mechanism of stimulated chiral light-matter interactions, providing better understanding of light-matter interaction in biophysics, chiral sensing, and quantum biophotonics.